Improvement of sliding mode controller by using a new adaptive reaching law: Theory and experiment. (February 2020) - Brahmi, Brahim; Laraki, Mohamed Hamza; Brahmi, Abdelkrim; Saad, Maarouf; Rahman, Mohammad H.
Abstract: In this paper, a new sliding mode control (SMC) is applied to a physical nonlinear system. The novelty of this approach is related to the proposed reaching law by overcoming the main limitations of SMC. Unlike existing reaching laws, the suggested one can achieve high performance with significant reducing of a chattering problem and has a very fast convergence time of the system trajectories into the origin. This law benefits from the advantages and overcomes the limitations of both the exponential reaching law (ERL) and the conventional sliding mode control (SMC). Simulation results and comparison study with ERL and SMC are presented and applied on two degrees of freedom robot in order to show the advantage of the proposed adaptive reaching law. Experiments results are performed with electric cylinder (DC Motor) to confirm this proposition in real-time implementation. Highlights: The proposed SMC can achieve a high performance with significant reducing of a chattering problem. A new adaptive reaching law is proposed to achieve very fast reachability convergence. Experiments and comparative results are presented to prove the superior performance of the proposed controller.